THE GENUS SIGANUS IN THE COLLECTION OF THE NATIONAL INSTITUTE OF OCEANOLOGY (SIGANIDAE) - Burhanuddin, -; Martosewojo, Sularto; Hutomo, Malikusworo; Djamali, Asikin (Marine Research in Indonesia, 1975)
Ten species of the genus Siganus namely Siganus vulpinus, S. corallinus, S. spinus, S. oramin, S. javus, S. virgatus, S. puellus, S. chrysospilos, S. vermiculatus, and S. guttatus are available in the collection of the Lembaga Oseanologi Nasional (LON = National Institute of Oceanology). The description of each of these species is presented.